E-Government Based Public Service Innovation At The Investment Office And One-Stop Integrated Service (Dpmptsp) In Bengkulu City - Indari Indari; Yusuarsono Yusuarsono; Evi Lorita (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the e-government based public service innovation at the investment office and one-stop integrated service in Bengkulu city. This research is a qualitative research which is presented descriptively. Informants in this study amounted to 6 people consisting of: 3 key informants and 3 main informants. Data collection methodes through interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. Based on the results of research and discussion, it is known that e-government-based Public Service Innovation at the Bengkulu City Investment and One-Stop Integrated Service Office is seen from the theory of the Characteristics of Public Service Innovation: (1) The element of novelty, the policy issued by the government through the Bengkulu City DPMPTSP is that the service system already uses an online system through the website. (2) The positive benefits and impacts, for agencies, are that employees can be more assertive in carrying out the rules without having to meet face-to-face with applicants during the current pandemic because the agency has implemented an online licensing system. For the community, it is easier for the applicant's business because there is no need to manually process files because an online system has been implemented through the website. (3) Providing a solution to the problem, the solution provided by the Bengkulu City DPMPTSP is that the agency facilitates computers, scanners and assistance to assist applicants in conducting business permits. (4) Continuous, the application of technology in DPMPTSP will be sustainable because it can facilitate licensing applications. (5) Compatibility, Employees at DPMPTSP adjust e-government licensing services by following established regulations, namely Government Regulation No. 24 of 2018 concerning Electronically Integrated licensing services.